Wonderfully Wordless: The 500 Most Recommended Graphic Novels and Picture Books - Martin, William Patrick (Rowman & Littlefield Publishers, 2015)
Wonderfully Wordless: The 500 Most Recommended Graphic Novels and Picture Books is the first comprehensive best book guide to wordless picture books (and nearly wordless picture books). It is an indispensable resource for parents and teachers who love graphic storytelling or who recognize the value of these exceptional books in working with different types of students, particularly preschool, English as a Second Language (ESL), and special needs, and creative writers. Every age group will benefit from Wonderfully Wordless, from babies and toddlers encountering their first books, to elementary age children captivated by the popular fantasy and adventure themes, to teenagers attracted to graphic novels because of their more intense content and comic book format. Even adults who are not yet readers will benefit from this uniquely authoritative resource because it will provide a bridge to literacy and give them books that they can immediately share with their children. Wonderfully Wordless is the ultimate guide to wordless and almost wordless books. Its 500 exemplary titles are a composite of 140 sources including recommendations from reference books, award lists, book reviews, professional journals, literary blogs, and the collections of many of the most prominent libraries in the United States and the English-speaking world. The US libraries include the Boston Public Library, Carnegie Library of Pittsburgh, Denver Library, New York Public Library, and Seattle Public Library, as well as the academic libraries at Bank Street College, Miami University, Michigan State University, Penn State University, Stanford University, and University of Chicago. The international libraries include the University of Oxford, British Council Library India, British Library, Hong Kong Public Libraries, National Library of the Philippines, Toronto Public Library, Trinity College Library (Dublin), Vancouver Public Library, and the National Library of New Zealand. The 500 books included here are generated from a database with 7,300 booklist entries. In essence, the ranked list emerging from this compilation will constitute “votes” for the most popular titles, the ones most experts agree are the best. By pooling the expertise from the US and other English-speaking countries, Wonderfully Wordless is an unrivaled core list of classic and contemporary titles. This authoritative reference book conveys not the opinion of one expert, but the combined opinions of a legion of experts. If a single picture is worth a thousand words, then a multitude of the picture-only texts is worth a compendium. Wonderfully Wordless is organized by theme and format and readers should have no problem zeroing in on their favorite topics. There are thirty-one chapters organized by topics such as Christmas Cheer, Character Values, Comedy Capers, Pet Mischief, Creative Journeys, Fascinating Fantasies, and Marvelous Mysteries. There is a full spectrum of wordless fiction and nonfiction, concept books, visual puzzles, board books, cloth books, woodcut novels, graphic novels, and more.